Business Model Canvas : Auto Vision (AV) Optical Centre / Anis Nur Izzati Syaffrizal - Syaffrizal, Anis Nur Izzati (2020)
Auto Vision (AV) Optical Centre has new product to introduce to the consumers which is Auto Focus glasses. My business decided to supply glasses since it parallels with customers‟ demand whose had short-sightedness and long-sightedness at the same time. Auto Focus glasses is a liquid based lenses made up of glycerine, a thick clear liquid, enclosed in flexible membranes. The glasses‟ liquid lenses change shape according to the distance of objects, making reading glasses and bifocals unnecessary